The doors of the ocean : hope for the hurting - O'Callaghan, John T; Scott, Stuart ([Charlestown, New South Wales] : John O'Callaghan, 2024)
This book is a reflective and contemplative book, created for adults who are seriously suffering; it comprises of reflective prose, short stories, poetry and also professional black & white photography. In part, it is a response to the royal commission which began here in my home town of Newcastle. The book is high end Arts production, hardback, section sewn, with thick soft cream papers, running to almost 200 pages. It is for all those who have run out of hope and those who are lovingly looking after their suffering loved ones.
Prepublication record (machine generated from publisher information)
Keywords: Grief; Loss..; Pastoral theology; Pastoral counseling; Psychology and religion